The Synthesis and Biological Evaluation of Multifunctionalised Derivatives of Noscapine as Cytotoxic Agents. Issue 2 (11th December 2013) - DeBono, Aaron J.; Mistry, Sarah J.; Xie, Jinhan; Muthiah, Divya; Phillips, Jackson; Ventura, Sabatino; Callaghan, Richard; Pouton, Colin W.; Capuano, Ben; Scammells, Peter J.
Abstract Noscapine, a phthalideisoquinoline alkaloid derived from Papaver somniferum, is a well‐known antitussive drug that has a relatively safe in vitro toxicity profile. Noscapine is also known to possess weak anticancer efficacy, and since its discovery, efforts have been made to design derivatives with improved potency. Herein, the synthesis of a series of noscapine analogues, which have been modified in the 6′, 9′, 1 and 7‐positions, is described. In a previous study, replacement of the naturally occurring N‐methyl group in the 6′‐position with an N‐ethylaminocarbonyl was shown to promote cell‐cycle arrest and cytotoxicity against three cancer cell lines. Here, this modification has been combined with other structural changes that have previously been shown to improve anticancer activity, namely halo substitution in the 9′‐position, regioselective O‐demethylation to reveal a free phenol in the 7‐position, and reduction of the lactone to the corresponding cyclic ether in the 1‐position. The incorporation of new aryl substituents in the 9′‐position was also investigated. The study identified interesting new compounds able to induce G2/M cell‐cycle arrest and that possess cytotoxic activity against the human prostate carcinoma cell line PC3, the human breast adenocarcinoma cell line MCF‐7, and the human pancreatic epithelioid carcinoma cell line PANC‐1. In particular, the ethyl urea cyclic ether noscapinoids and a compound containing a 6′‐ethylaminocarbonyl along with 9′‐chloro, 7‐hydroxy and lactone moieties exhibited the most promising biological activities, with EC50 values in the low micromolar range against all three cancer cell lines, and these derivatives warrant further investigation.